Features of the development of inbound and outbound educational tourism: the experience of Kazakhstan - Mamrayeva, D.G.; Tashenova, L.V.; Ayaganova, M.P.; Togaibayeva, L.I. (BUKETOV BUSINESS REVIEW, 2023)
Object: to identify the main trends in the development of inbound and outbound educational tourism in Kazakhstan, to determine its structure, flows and capacity. Methods: a descriptive method, the main trends in educational tourism were studied, in particular, the dynamics of the contingent of foreign students in the country's universities was reflected, the geography was described and the capacity of inbound and outbound tourism was shown; method of analysis, which made it possible to assess and update information on the main trends in educational tourism in Kazakhstan; method of generalization and structuring – common properties and key features of the analyzed objects were established. Findings: the article reveals the main trends in educational tourism in Kazakhstan reflects the dynamics of the contingent of foreign students in the country's universities, describes the geography and shows the capacity of inbound and outbound educational tourism; on the basis of statistical indicators, an assessment was given and information on academic mobility was updated. Conclusions: despite the insignificant share of foreign students, the interest in Kazakhstani educational programs from foreign students is growing every year; there is a regional differentiation in the development of educational tourism in the country; the number of Kazakhstani universities that implement academic mobility programs is increasing annually, including in an online format; the geography of outbound and inbound educational tourism is expanding; people come to Kazakhstan mainly for the purpose of obtaining education in the areas of “Health care and social security (medicine)”, “Pedagogical sciences”, “Business, management and law”; less popular – “Agriculture and bioresources”, “Veterinary”.